Minimizing DILI risk in drug discovery — A screening tool for drug candidates. Issue 1 (25th December 2015) - Schadt, S.; Simon, S.; Kustermann, S.; Boess, F.; McGinnis, C.; Brink, A.; Lieven, R.; Fowler, S.; Youdim, K.; Ullah, M.; Marschmann, M.; Zihlmann, C.; et al.
Abstract: Drug-induced liver injury (DILI) is a leading cause of acute hepatic failure and a major reason for market withdrawal of drugs. Idiosyncratic DILI is multifactorial, with unclear dose-dependency and poor predictability since the underlying patient-related susceptibilities are not sufficiently understood. Because of these limitations, a pharmaceutical research option would be to reduce the compound-related risk factors in the drug-discovery process. Here we describe the development and validation of a methodology for the assessment of DILI risk of drug candidates. As a training set, 81 marketed or withdrawn compounds with differing DILI rates – according to the FDA categorization – were tested in a combination of assays covering different mechanisms and endpoints contributing to human DILI. These include the generation of reactive metabolites (CYP3A4 time-dependent inhibition and glutathione adduct formation), inhibition of the human bile salt export pump (BSEP), mitochondrial toxicity and cytotoxicity (fibroblasts and human hepatocytes). Different approaches for dose- and exposure-based calibrations were assessed and the same parameters applied to a test set of 39 different compounds. We achieved a similar performance to the training set with an overall accuracy of 79% correctly predicted, a sensitivity of 76% and a specificity of 82%. This test system may be applied in a prospective manner to reduce the risk of idiosyncratic DILI of drug candidates. Graphical abstract: Highlights: The risk of idiosyncratic DILI of drug candidates can be reduced by combining assays covering different mechanisms. The strategy is applicable to early stages when risk mitigation is still possible. Dose- and exposure-based calibration of the assays leads to markedly improved accuracy.